Strengthening Coastal and Marine Climate Resilience Through Upland and Coastal Ecosystem Based Adaptation and Community Engagement in the Caribbean - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2023)
Descripción: To improve marine-coastal resilience, this project focuses on community engagement and implementation of nature-based solutions to reduce the upland drivers of degradation and conserve ecosystems and their services; raise awareness of climate risks; provide additional nature-based livelihood opportunities, and facilitate monitoring of ecosystem health to ensure sustainability. Objetivo General: To restore ecosystem health of upland-coastal environments to strengthen marine-coastal climate resilience while improving sustainable livelihood opportunities of communities.